Mapping an evidence-based end-of-life care framework for older adults in Chinese nursing homes: protocol for a scoping review - Zhao, Yuanyuan; Tu, Yuehua; Chew, Boon How; Gacasan, Eva Marie (BMJ Publishing Group, 2024)
Introduction End-of-life care is essential for older adults aged ≥60, particularly those residing in long-term care facilities, such as nursing homes, which are known for their home-like environments compared with hospitals. Due to potential limitations in medical resources, collaboration with external healthcare providers is crucial to ensure comprehensive services within these settings. Previous studies have primarily focused on team-based models for end-of-life care in hospitals and home-based settings. However, there is a lack of sufficient evidence on practices in such facilities, particularly for Chinese older adults. The aim of this scoping review is to map the existing literature and inform the development of an appropriate care framework for end-of-life care in nursing homes. The focus of this article will be on the scope of services, guidelines for decision making, roles within interdisciplinary teams, and the practical feasibility of care provision. Methods and analysis A systematic search will be conducted across nine electronic databases: PubMed, Scopus, EMBASE, Cochrane, PsycINFO, ERIC, CINAHL, China National Knowledge Infrastructure (CNKI), and Wanfang Data. The search will identify literature published in English and Chinese from January 2012 onwards. Articles will be selected based on their relevance to older adults aged ≥60 with disabilities or life-threatening chronic conditions receiving end-of-life care in nursing homes or similar settings. The data extraction process will be guided by the Canadian Hospice Palliative Care Association model (CHPCA) and the Respectful Death model. Qualitative data analysis will be performed using a framework method and thematic analysis, employing both inductive and deductive approaches, with three reviewers participating in the review process. Ethics and dissemination Ethical approval is not required because the data for this review is obtained from selected publicly available articles. The results will be disseminated through publications in peer-reviewed journals and presented at relevant conferences. Furthermore, the findings will be shared with policymakers and healthcare professionals engaged in end-of-life care to inform practice and decision making.